Apollo and Marsyas, and Other Poems - Lee-Hamilton, Eugene, 1845-1907 (Salt Lake City, UT : Project Gutenberg, 2022)
"Apollo and Marsyas, and Other Poems" by Eugene Lee-Hamilton is a collection of poems written in the late 19th century. The poems draw on themes of mythology, the contest between artistic expression and emotional turmoil, and human experiences intertwined with nature and spirituality. The titular poem "Apollo and Marsyas" explores the tension between the divine and the primal, illustrating the struggles between the god Apollo and the satyr Marsyas, along with other narratives reflecting deeper philosophical discourses. At the start of the collection, the introduction sets the stage for a poetic exploration of the dualities of existence - the serene beauty represented by Apollo and the wild, untamed nature symbolized by Marsyas. The poems depict the struggle for recognition and understanding in the realm of art and nature, reflecting on the choices and conflicts faced by humanity. The vivid imagery and lyrical language invite readers to contemplate the tension between light and darkness, beauty and despair, in the unfolding stories of both gods and mortals. (This is an automatically generated summary.)
Release date is 2022-01-01
Tim Lindell, Chuck Greif and the Online Distributed Proofreading Team at https://www.pgdp.net (This book was produced from images made available by the HathiTrust Digital Library.)
Keywords: English poetry -- 19th century